PENGEMBANGAN DIGITAL GOVERNANCE DALAM TATA KELOLA PEMERINTAHAN DESA Di DESA PONTANG - Cadith, Juliannes; Yulianti, Rina; Janurina, Andi Moch (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Development of Digital Governance in Village Governance is urgently needed. The community is used to internet media, because during the Covid-19 period, the government carried out public services online, as well as information provided through internet media. So that all government and community organizations, especially in villages, become accustomed to using applications provided by the local government. Likewise with Pontang Village which has advantages or potential that can be explored further and can be one of the inputs in improving people's welfare. The results of research that has been done by researchers, one of the important things is the desire of the community to get service information quickly through online media. Because of that, researchers want to make a program or application that can make it easier for the community to get information, besides that village officials can also store village data in the application. So that good village governance in digital governance can work.